Legislative Scrutiny : Police, Crime, Sentencing and Courts Bill (Part 4): The criminalisation of unauthorised encampments : Fourth Report of Session 2021–22.: Police, Crime, Sentencing and Courts Bill (Part 4): The criminalisation of unauthorised encampments : Fourth Report of Session 2021–22. Report / Volume 1, ([2021-07-02]) - Unknown
No abstract available